(untitled) (Journal of Computational Mathematics, 1999)
In this paper, the periodic initial value problem for the following class of nonlinear schr00f6dinger equation of high order i00a02202u2202t + (20131)^m 2202^m2202x^m ( a(x) 2202^mu2202x^m ) +00a003b2(x)q(|u|^2)u + f (x; t)u = g(x; t) is considered. A leap-frog finite difference scheme is given, and convergence and stability is proved. Finally, it is shown by a numerical example that numerical result is coincident with theoretical result.00a0